A framework for successful delivery of stakeholder management in public-private partnership infrastructure projects in Malaysia / Sakinah Khalidah Kaharuddin - Kaharuddin, Sakinah Khalidah (2021)
Public-Private Partnership (PPP) has been identified as a procurement method that brings the public and private sectors together to facilitate the delivery of infrastructure projects and services. PPP manages complex projects and involves multiple stakeholders. Stakeholders in PPP project need to be properly managed to achieve the project goals, minimising risk and accommodate stakeholder interest. Stakeholder management is about relationship between organisation and its stakeholders. Poor management of stakeholder could lead to project failure. Thus, requires appropriate framework in addressing an effective stakeholder management in PPP infrastructure projects. This research aims to improve the process of stakeholder management in PPP by developing a successful delivery framework for the stakeholder in infrastructure projects. The research entails three (3) main objectives which include; a) to identify the implementation and challenges of stakeholder management in PPP infrastructure projects, b) to examine success factors towards successful implementation of stakeholder management in PPP infrastructure projects, and c) to develop an appropriate framework for the successful delivery of stakeholder management in PPP infrastructure projects. The research involved in four (4) stages of stakeholder management such as stakeholder analysis, stakeholder engagement, stakeholder management action plan and stakeholder management monitoring. A triangulation method involves interview, questionnaire survey, and expert panel interview were adopted in this research. The semistructured interviews were conducted to obtain general perspective from nine (9) concession companies involved PPP in Malaysia. Then the quantitative analysis through survey was conducted to 43 respondents from various stakeholder’s background namely public authority, consultant, contractors and financier. Five (5) expert interviewers concluded the triangulation approach to ensure a robust and reliable data. The finding highlights on four (4) stakeholder management issues that need to be focused in PPP infrastructure projects. These include the need for a good stakeholder management process, the strategy to engage the stakeholders through clear and honest communication, a proper project communication plan to oversee overlapping in the process, and to monitor relationships of stakeholders during operations A framework has been established to assist the stakeholder in PPP infrastructure project to achieve the successful delivery of stakeholder management.